Effect of PCSO-524 on OA biomarkers and weight-bearing properties in canine shoulder and coxofemeral osteoarthritis - Kumpanart Soontornvipart (2018)
This study was designed to compare the therapeutic benefits of a compound of omega-3 fatty acids from the New Zealand green-lipped mussel (Perna canaliculus) (PCSO-524) and omega-3 fatty acids in fish oil on clinical outcomes and osteoarthritis biomarkers (chondroitin sulfate WF6 epitope) in 66 dogs that had osteoarthritis (OA); 39 dogs with OA hip joints, 15 dogs with OA shoulder joints and 12 dogs with OA shoulder and hip joints. The animals were presented at the Small Animal Hospital, Faculty of Veterinary Science, Chulalongkorn University. The dogs were allocated into two groups randomly. One group received PCSO-524 (n = 33) and the other group received fish oil (n = 33), administered orally for 24 weeks. Serum OA biomarkers (WF6), lameness scores, weight-bearing scores, range of motion (ROM) and peak vertical force gait analysis were evaluated before treatment and two, four, eight, 12, 16, 20 and 24 weeks after the treatment began. The mean of serum WF6 of the PCSO-524 group (262.46±118.06 ng/ml) was significantly (p < 0.05) less than that of the fish oil group (324.76±133.65 ng/ml) after 24 weeks of administration. The lameness scores, weight-bearing scores, peak vertical force gait analysis results and ROM improved significantly within two weeks after the administration of PCSO-524 began, while there was no statistically significant improvement in any of the parameters of the fish oil group after 12 weeks. After week four, the lameness and weight-bearing scores and gait analysis results of the PCSO-524 group improved significantly by comparison with the fish oil group. In conclusion, the PCSO-524 administration led to good clinical outcomes and laboratory results of osteoarthritis of the shoulder and hip joints in dogs.